Digital Marketing Strategies To Increase Online Business Sales Through Social Media - Niko Garuda Adiyono; Tantri Yanuar Rahmat; Rina Anindita (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
Technological developments have brought new media related to the internet. The internet is currently a necessity for many people around the world because with the internet, information can be conveyed quickly and easily. In the world of business is also entered by the internet. The internet creates something new, one way of marketing product. A businessman finds the latest marketing strategy by creating digital content for the products they offer and they will distribute it on social media so that more people and potential consumers will see and know about the product. Social Media is an application that provides video making features along with very interesting and easy to use effect features. That way, not a few online business people take advantage of the golden opportunity to use the application. Social Media as a platform to develop their business a through digital content.